Haemophilia: An Update (Journal of Bangladesh College of Physicians and Surgeons, 2007)
Haemophilia has been recognized a clinical entity since Biblical times when there was repeated history of death from circumcisional bleeding in male siblings. Recent advances in protein chemistry and recombinant DNA technology have produced a comprehensive account both of normal coagulation and of the molecular genetics of some type of haemophilia. Haemophilia is a hereditary coagulation disorders usually of male associated with serious bleeding which is transmitted by healthy women. It is caused by a reduction in the amount or activity of factor VIII. This protein serves as a cofactor for factor IX in the activation factor X in the coagulation cascade. Haemophilia A & Haemophilia B exhibit a wide range of clinical severity that correlate well the level of factor VIII activity. Those with less than 1% of normal activity develop severe disease; levels between 2% and 5% of normal are associated with moderate disease; and patient with 6% to 50% of activity developed mild disease. The variable degrees of factor VIII deficiency are largely explained by heterogenecity in the causative mutation. Several genetic lesions - deletions, nonsense mutations that create loop codons, splicing errors have been documented. Most severe deficiencies result from an unusual inversions involving X chromosomes that completely abolishes the synthesis of factor VIII. Haemophilia is inherited as X-linked recessive trait, and thus occurs in male and both homozygous and heterozygous female. Approximately 30% of patients have no family history; their disorder is presumably caused by new mutation. In this review article we want to highlight the recent aspects of haemophilia including the occurrence of haemophilia in female, genetic causes of coagulation factor deficiency, carrier detection and antenatal diagnosis, upto date diagnostic tools of this hereditary coagulation disorder as well as management of haemophiliac patients in special situation like circumcision, road traffic accident, minor and major surgery. (J Bangladesh Coll Phys Surg 2007; 25 : 29-37)